Environmental Mechanisms to Improve the Quality Control System for the Enhancement of Production Competitiveness - BELONOZHKO, Lydia N.; IGNATENKO, Valentina A.; MAYER, Vladimir V. (Journal of Environmental Management and Tourism; Vol 10 No 3 (2019): JEMT Volume X Issue 3(35) Summer 2019, 2019)
The purpose of the article is to study the specifics of creating, promoting products and ecology control of quality in the practice of domestic enterprises, as well as forming recommendations for improving the quality system of environmental management to improve product competitiveness in modern conditions. In the process of research, system analysis, economic analysis, ecology analysis and synthesis, statistical and analytical methods, generalization, systematization, structuring were used. It is revealed that the increasing competition, the diversity of the same goods in the same price segment directs enterprises to search for new ways to create additional competitive advantages aimed at winning customer loyalty. The current situation requires quality management at all stages of the promotion of food to the consumer – from the production of agricultural products, their processing, transportation and storage to the sale to the public. The article studied practical experience. Problems were identified, theoretical and methodological aspects of the subject of research were investigated, on the basis of which scientific, methodological and practical guidelines were developed for structuring the system of product quality ecology management, choosing directions for improving the management of enterprise competitiveness through improving product quality.